2017
DOI: 10.1002/adem.201700818
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dynamically Recrystallized Grains on Rare Earth Texture in Magnesium Alloy Extruded at High Temperature

Abstract: This work investigates texture evolution in an Mg-3Gd-0.2Al alloy during extrusion and after annealing at 500 C. It shows that the dynamically recrystallized (DRX) grains formed in grain boundaries and twins have different influence on texture evolution. After extrusion, the DRX grains that nucleated at grain boundaries have texture distributing from <20-21> || ED to <11-21> || ED, while these in twins do from <10-12> || ED to <11-22> || ED. After further annealing process, the <11-21> || ED component is stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Due to the phenomenon of particle-stimulated nucleation (PSN), precipitates also influence grain size, especially if they have a high volume fraction [ 11 ]. Owing to the hexagonal close-packed (HCP) structure of Mg alloys, their mechanical behavior also depends on the activation of different dislocation slip systems, which is influenced by their texture [ 12 , 13 , 14 ]. Li et al proposed that a Yb addition effectively refined recrystallized grains and yielded dense Mg–Zn–Yb nanoprecipitates that could inhibit grain boundary migration, and also could promote the formation of the RE texture component [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the phenomenon of particle-stimulated nucleation (PSN), precipitates also influence grain size, especially if they have a high volume fraction [ 11 ]. Owing to the hexagonal close-packed (HCP) structure of Mg alloys, their mechanical behavior also depends on the activation of different dislocation slip systems, which is influenced by their texture [ 12 , 13 , 14 ]. Li et al proposed that a Yb addition effectively refined recrystallized grains and yielded dense Mg–Zn–Yb nanoprecipitates that could inhibit grain boundary migration, and also could promote the formation of the RE texture component [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, rare earth can be connected to electron‐rich atoms through coordination bond ,. In view of the above excellent performance, rare‐earth compounds are mostly used for electrode materials, supercapacitors, catalyst material and so on. However, the research on tribology is relatively few.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the texture is related with the alloying elements. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] However, the texture evolution of Mg alloy with the high content of Gd during annealing has not been investigated in detail in previous literature. [1][2][3][4] While the rare earth (RE) containing Mg alloys exhibit weaker basal textures during extrusion compared with the RE-free alloys such as AZ31 and AZ61.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] It has been reported that addition of little La or Gd element can produce a weak texture with <11-21>||ED orientation during lower extrusion temperature, [10] and the extruded rods with high content of Gd exhibit a weak texture with <0001>||ED orientation. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] However, the texture evolution of Mg alloy with the high content of Gd during annealing has not been investigated in detail in previous literature. The texture evolution of strong texture with <0001>?ED in conventional extruded Mg alloys during annealing has been widely reported.…”
mentioning
confidence: 99%